Effectiveness of Ondansetron in comparison to Domperidone for treating vomiting in acute gastroenteritis among children in a tertiary care hospital setting: A quasi-experimental study - Muddassir Zafar; Wajiha Rizwan; Muhammad Rafique; Shahid Mahmood; Yasir Javed (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: There is inconsistent evidence on using antiemetic drugs (ondansetron and domperidone) in children with vomiting associated with gastroenteritis having dehydration. The study’s objective was to compare the effectiveness of oral domperidone with ondansetron for treating vomiting during acute gastroenteritis in children with either mild or moderate dehydration. METHODOLOGY: This non-controlled quasi-experimental study was conducted at Allama Iqbal Teaching Hospital, Sialkot, in the department of Pediatrics from 1st October 2019 to 31st December 2019. Sixty children aged 1-12 years having acute gastroenteritis, with mild or moderate dehydration after the failure of initial oral rehydration therapy, were included. Children in-group A (n=30) received a single dose of an orally disintegrating tablet of ondansetron, and children in-group B (n=30) were treated with domperidone. The absence of vomiting for 6 hours and subsequent successful rehydration in these two groups was the primary outcome. The Chi-square test was applied to compare the frequency of primary outcome between the ondansetron and domperidone groups, considering p-value ≤0.05 was considered statistically significant. RESULTS: The mean age of patients was 4.4±1.8 years in group A compared to 5.1±2.7 years in group B. Oral Ondansetron was successful in controlling vomiting in 19(63.4%) patients compared to 11(36.6%) in domperidone group (p=0.39). CONCLUSION: The single dose of oral ondansetron compared to domperidone was significantly effective in controlling the vomiting in-patient with acute gastroenteritis presented with either mild or moderate dehydration, resulting in effective oral rehydration subsequently.